Categorising social enterprise business model - case studies from Malaysia - Sim, Vanessa Xiang Jing (2022)
Social enterprise has gained increasing attraction in Malaysia. This study aims to understand the type of business model adopted by social enterprises in Malaysia and develop a framework for assessing the business model. Specifically, it investigates the parameters and factors that enable social entrepreneurs to achieve social or environmental outcomes and earn revenue.